2021
DOI: 10.3390/app11083384
|View full text |Cite
|
Sign up to set email alerts
|

Gamification in IT Service Management: A Systematic Mapping Study

Abstract: Despite the benefits of adopting IT Service Management (ITSM) reference models, such initiatives do not always produce the expected results. The research literature in this area concludes that motivation, engagement, skills, experience, performance and willingness to change of the personnel involved are among the critical factors for an effective ITSM implementation. Gamification has the capability to improve people’s motivation and engagement and to drive people’s behavior to meet the objectives set. Besides,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Leaderboards have been shown that they are effective both in terms of team building and team reinforcement [13]. They are also usually found to be one of the most utilised elements in gamification [20], [21]. More specifically, leaderboards can be useful for encouraging meetings, social gatherings, informal communications, technical discussions, and monitoring purposes [22].…”
Section: Background: Approaches To Gamification In Software Engineeri...mentioning
confidence: 99%
“…Leaderboards have been shown that they are effective both in terms of team building and team reinforcement [13]. They are also usually found to be one of the most utilised elements in gamification [20], [21]. More specifically, leaderboards can be useful for encouraging meetings, social gatherings, informal communications, technical discussions, and monitoring purposes [22].…”
Section: Background: Approaches To Gamification In Software Engineeri...mentioning
confidence: 99%
“…Gamification is defined as using gaming techniques in non-gaming environments. Although it is a recent topic, some authors have already addressed it in certain areas, namely: in the workplace as motivational strategies, in teaching, in the fashion industry, in engineering, in health, or marketing (Aparicio et al 2021;Carlier et al 2021;Lucassen and Jansen 2014;Reis et al 2020;Trinidad et al 2021). Co-creation is a strategy of interaction between the company, customers, suppliers and even competitors, which aims at the participation of these agents in the creation of products/services, that is, in the creation of value (Lucassen and Jansen 2014;Rodrigues et al 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…al., 2020;Serrano et al, 2021). Due to the popularity of ITSM frameworks, an increasing number of companies are implementing reference models to improve their ITSM processes(Trinidad, Orta & Ruiz, 2021) Kubiak & Rass (2018). state that ITSM frameworks and processes bring together a set of best practices for the ITS lifecycle, and a best practice is defined as a method or technique that consistently performs better than its alternatives.…”
mentioning
confidence: 99%